Chondromyxoid Fibroma of the Lateral Malleolus a En-Block Excision and Steinmann Pin Stabilisation of the Ankle (Global Journal of Medical Research, 2018)
We report a case of a 25-year-old male with a chondromyxoid fibroma located in the lateral malleolus. This may be considered to be a rare tumour in an unusual location. The tumour was treated via an en-block excision and the ankle was stabilised with a Steinmann pin. The original plan was that the Steinmann pin was to provide temporary stabilisation while awaiting definitive histology. Ankle arthrodesis was supposed to be performed at a later date if the histology confirmed a benign tumour. Delayed wound healing resulted in the Steinmann pin being left in situ for twelve weeks. Two years post Steinmann pin removal; there was no clinical or radiological evidence of tumour recurrence or ankle instability. The patient was satisfied with his function and a secondary procedure was deemed unnecessary. The surgical options for benign distal fibular tumours including chondromyxoid fibroma are discussed below.
Keywords: chondromyxoid fibroma; lateral malleolus; excision; reconstruction